THE PERSONALITY OF THE MAIN CHARACTER IN HAIFA BITAR’S SHORT STORY “KAFANU AL-USTADZI”: A LITERARY PSYCHOLOGY STUDY: KEPRIBADIAN TOKOH UTAMA DALAM CERPEN “KAFANU AL-USTADZI” KARYA HAIFA BITAR: KAJIAN PSIKOLOGI SASTRA - Tarishah Fatihah Ikhlas; Muhammad Walidin; Ulil Albab; Isnaini Rahmawati (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Psychoanalysis is one of the literary research theories that discusses the human psyche. This study aims to analyze the characterization and personality structure of the main character in Haifa Bitar's short story Kafanu Al-Ustadzi using Burhan Nurgiyantoro's structural theory and Sigmund Freud's theory which focuses on the forms of Id, Ego, and Superego in the story. Using a qualitative descriptive method, data was obtained through selected excerpts from the short story. The research findings identified that the characterization of the character Aku is divided into five types, namely first as the main character; second, as a protagonist; third, as a round character; fourth, as a developing character; and fifth, as a neutral character. The forms of the main character's traits include patience, persistence, anger, attentiveness, unstable, hatred, and vengeance. This research also reveals the personality structure of the main character who has a complete personality structure, although Id is more dominant than Ego and Superego with the amount of data Id 4 data, Ego 2 data, and Superego 3 data. This research contributes to the development of Arabic literature studies by analyzing characterizations and psychological aspects in literary works so as to expand the scope of Arabic literary theory.